SIMULATION STUDY ON THE COMPARISON OF ERROR CORRECTION MODEL AND AUTOREGRESSIVE DISTRIBUTED LAG MODEL FOR NON-NORMALLY DISTRIBUTED DATA - ALEMHO, J. E.; ADENOMON M. O. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
This study investigates simulation study of the comparison between Error Correction Model (ECM) and Autoregressive Distributed Lag (ARDL) Model on non-normally distributed data. The study utilized both simulated data with 5000 iterations and the real life data of inflation rate and unemployment rate in Nigeria from a period of 1981 to 2016. The Augmented-Dickey Fuller (ADF) test revealed that inflation and unemployment are stationary at first difference while cointegration test and bound testing revealed an existence of long run relationship between the macroeconomic variables. The Root Mean Square Error (RMSE) of the simulated data of the two models were compared and the normality test (Jarque-Bera test) shows that the variables are nonnormally distributed. The study revealed that the ARDL model outperforms the ECM model for both the real life data and simulated data and that there is evidence of both short and long run relationship between inflation rate and unemployment rate in Nigeria. It also revealed that there is causality relationship between inflation rate and unemployment. The study therefore recommended based on the findings that the Central Bank of Nigeria should pursue monetary policy that is consistent with the maintenance of a realistic and stable inflation rate in order to reduce the unemployment rate in Nigeria and the government should formulate adequate economic policies to stimulates and sustain the economic growth. In addition, the inflation rate should adequately check to achieve viable economy.